The Application Of Transparent And Immediate Principles In Land Sale And Purchase Agreement (Study Of Court Decision Number 50/Pdt.G/2022/PN.Smn; 102/PDT/2022/PT.YYK, AND 89/PDT.G/2022/PN KLN) - Eko Rial Nugroho (Universitas Islam Indonesia, 2023)
Pursuant to established norms within customary law, the buying and selling of land constitutes a transfer of land rights that is both transparent and immediate. This transfer of right occurs simultaneously upon the buyer's payment following the principle of direct exchange or concrete transaction. The principle of land transactions shares similarities with general contractual agreements, necessitating adherence to Article 1320 of the Indonesian Civil Code. The sale and purchase of land under customary law are often witnessed solely by relatives, kin, and close neighbors, without the involvement of government officials. Claims may arise asserting that the process of transferring land rights was conducted in violation of regulations, particularly on the lack of official witnesses. This article employs a qualitative approach, involving the processing and analysis of data with a profound understanding of the researched issue. The normative juridical approach draws the prevailing legal provisions or employs the doctrinal legal method, and encompasses legal theories and expert opinions relevant to the discussed matter. The findings of this research underscore the prevailing agrarian law in Indonesia, which is rooted in customary law, as long as it aligns with national and state interests. Therefore, as long as the sale and purchase process is conducted genuinely, transparently, and immediately, and adheres to the principles of clarity and immediacy it is considered legally valid and is thereby irrevocable.Keywords: Land Purchase Agreement, The Principle of Transparency, The Principle of Immediacy. Penerapan Asas Transparan Dan Kedekatan Dalam Perjanjian Jual Beli Tanah (Studi Putusan Pengadilan Nomor 50/Pdt.G/2022/PN.Smn; 102/PDT/2022/PT.YYK, DAN 89/PDT.G/2022/ PN KLN) AbstrakBerdasarkan norma-norma yang berlaku dalam hukum adat, jual beli tanah merupakan peralihan hak atas tanah yang bersifat transparan dan segera. Perpindahan hak ini terjadi bersamaan dengan pembayaran pembeli dengan prinsip pertukaran langsung atau transaksi konkrit. Prinsip transaksi tanah mempunyai persamaan dengan perjanjian kontrak pada umumnya, sehingga harus dipatuhi Pasal 1320 KUHPerdata. Jual beli tanah menurut hukum adat seringkali hanya disaksikan oleh sanak saudara, kerabat, dan tetangga dekat, tanpa keterlibatan pejabat pemerintah. Dapat timbul tuntutan yang menyatakan bahwa proses peralihan hak atas tanah dilakukan dengan melanggar peraturan, khususnya karena tidak adanya saksi resmi. Artikel ini menggunakan pendekatan kualitatif, yang melibatkan pengolahan dan analisis data dengan pemahaman mendalam tentang masalah yang diteliti. Pendekatan yuridis normatif mengambil ketentuan hukum yang berlaku atau menggunakan metode hukum doktrinal, serta mencakup teori-teori hukum dan pendapat para ahli yang relevan dengan hal yang dibicarakan. Temuan penelitian ini menggaris bawahi hukum agraria yang berlaku di Indonesia, yang berakar pada hukum adat, sepanjang sejalan dengan kepentingan nasional dan negara. Oleh karena itu, sepanjang proses jual beli tersebut dilakukan dengan sungguh-sungguh, transparan, dan segera, serta berpegang pada asas kejelasan dan kesegeraan, maka dianggap sah secara hukum dan tidak dapat ditarik kembali.Kata Kunci: Perjanjian Jual Beli Tanah, Prinsip Transparansi, Prinsip Kedekatan.